Green Synthesis of Nanoparticles and Their Biomedical Applications: A Review - S. J. Patil, (International Journal of Scientific Research in Science and Technology, 2024)
Green synthesis, which uses plant extracts, can be used to generate metallic nanoparticles that have a lot of uses in biomedicine. This approach is not only good for the environment, but it is also cheap and long-lasting. These nanoparticles have shown promise in a number of related areas, in addition to their possible uses in regenerative medicine, immunotherapy, wound healing, tissue repair, and diagnostics. Nanoparticles synthesised by ecologically benign processes are beneficial in environmental remediation and biological sciences due to their antioxidant, antibacterial, antifungal, and antiviral properties. Green synthesis is a procedure that uses plant extracts as stabilisers and reducers to make nanoparticles that are safe for people to eat and may be used in many different ways. Researchers have discovered that nanoparticles generated by eco-friendly methods exhibit reduced toxicity and enhanced biological activity relative to those made via chemical processes. This underscores the necessity of utilising eco-friendly production techniques for nanoparticles.
Keywords: nanoparticles; green methods; biological activity; biomedical applications